PERLINDUNGAN HUKUM TERHADAP WARTAWAN YANG MENGALAMI TINDAK PIDANA KEKERASAN DALAM MENJALANKAN TUGAS PROFESI - Elfrida, Eisabet Sri; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The development of mass media today is growing rapidly to be accepted and consumed by the public, whether news that smells negative or positive. The press and mass media are also very supportive for the success of development and the achievement of a just and prosperous society based on Pancasila in addition to the facilities that support the implementation of other development.As for the problems in this research is the cause of violent crime against journalists who are carrying out duties and professions. The legal rules concerning violent crime committed against journalists who are carrying out their duties and profession and legal protection against journalists who are subjected to criminal acts of violence in carrying out duties according to the Criminal Code and Law No. 40 of 1999. This research includes research normative law, including research on the inventory of positive law, legal principles, clinical law research, systematic legislation, synchronization of a legislation, legal history and comparative law.Legal arrangements against journalists of criminal acts of violence in performing professional duties Article 28 of the 1945 Constitution. Law Number 40 Year 1999 concerning the Press. Law Number 39 Year 1999 on Human Rights. Causes of violence against journalists are Internal Factors, Weak Regulation, Changes in legislation, Incompetence of journalists, Standards competence of journalists against changes in the laws of the press. External factors. Perpetrator of Persecution Not Understanding Journalist is a Profession Protected by Law and Constitution. Journalists who do not work in accordance with journalistic code of ethics and Law no. 40 of 1999. Press companies that have not been total in defending journalists. Criminal law policy against journalists in performing professional duties, namely: Penal Penal path, namely by applying criminal law (criminal law application). Non Penal The non penal path is done in a way that is: prevention without punishment, including the imposition of administrative sanctions and criminal and civil sanctions. Affects the public's view of crime and mass media development (influencing views of society on crime and punishment).Keywords: Legal Protection, Journalist-Crime of Violence, -Executing Profession Duties